First Viruses Infecting the Marine Diatom Guinardia delicatula - Arsenieff, Laure; Simon, Nathalie; Rigaut-Jalabert, Fabienne; Le Gall, Florence; Chaffron, Samuel; Corre, Erwan; Com, Emmanuelle; Bigeard, Estelle; Baudoux, Anne-Claire (Frontiers in Microbiology, 2019)
The marine diatom Guinardia delicatula is a cosmopolitan species that dominates seasonal blooms in the English Channel and the North Sea. Several eukaryotic parasites are known to induce the mortality of this species. Here, we report the isolation and characterization of the first viruses that infect G. delicatula. Viruses were isolated from the Western English Channel (SOMLIT-Astan station) during the late summer bloom decline of G. delicatula. A combination of laboratory approaches revealed that these lytic viruses (GdelRNAV) are small tailless particles of 35-38 nm in diameter that replicate in the host cytoplasm where both unordered particles and crystalline arrays are formed. GdelRNAV display a linear single-stranded RNA genome of ~9 kb, including two open reading frames encoding for replication and structural polyproteins. Phylogenetic relationships based on the RNA-dependent-RNA-polymerase gene marker showed that GdelRNAV are new members of the Bacillarnavirus, a monophyletic genus belonging to the order Picornavirales. GdelRNAV are specific to several strains of G. delicatula. They were rapidly and largely produced (< 12h, 9.34 x 104 virions per host cell). Our analysis points out the host’s variable viral susceptibilities during the early exponential growth phase. Interestingly, we consistently failed to isolate viruses during spring and early summer while G. delicatula developed important blooms. While our study suggests that viruses do contribute to the decline of G. delicatula’s late summer bloom, they may not be the primary mortality agents during the remaining blooms at SOMLIT-Astan. Future studies should focus on the relative contribution of the viral and eukaryotic pathogens to the control of Guinardia’s blooms to understand the fate of these prominent organisms in marine systems.